Quantifying Quality: What Can the U.S. News and World Report Rankings Tell us About the Quality of Higher Education? - Marguerite Clarke (Arizona State University, 2002)
Since their first appearance in 1983, the U.S. News and World Report rankings of colleges and graduate schools have generated much discussion and debate, from some declaring them among the best rankings ever published to others describing them as shallow, inaccurate, and even dangerous. The research presented here addresses two of the most common criticisms of the methodology used to produce these rankings. In particular, this study answers the following questions: What is the extent of change in U.S. News' ranking formulas across years and what are the implications for interpreting shifts in a school's rank over time? How precise is the overall score that U.S. News uses to rank schools and what are the implications for assigning schools to discrete ranks? Findings confirm critic's concerns in each of these areas, particularly in relation to the ranking of graduate schools of education. Based on these results, five recommendations are made for improving the interpretability and usefulness of the rankings.